2011
DOI: 10.1021/np200365z
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Talathermophilins from the Thermophilic Fungus Talaromyces thermophilus YM3-4

Abstract: Six indole alkaloids with various levels of prenylation were isolated from the thermophilic fungus Talaromyces thermophilus strain YM3-4. Their structures were identified by NMR and MS spectroscopic analyses. Compounds 1 and 2 are new analogues of the key versatile precursor notoamide E. Compound 3 is a novel analogue of preechinulin, and compound 4 was reported as a natural occurring cyclo(glycyltryptophyl) for the first time. The metabolite profile of this thermophilic organism displayed a biosynthetic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…Unlike notoamide B, metabolites tentatively identified by HPLC-MS as dihydrotalathermophilins A and B appear to be efficiently converted into the talathermophilins A and B, which, according to metabolite profiling, appear to be the end-products. Indeed these dihydrotalathermophilins A and B were recently structure elucidated 58b and named talathermophilin C and D. There were no indications of other metabolites with a bicyclo[2.2.2]diazaoctane ring system and/or any of the spiro -compunds of the notoamide type in Talaromyces thermophilus , where glycine or alanine analogues of the proline-derived metabolites discussed here could theoretically have been secondary metabolites in this themophilic species.…”
Section: Related Metabolites Lacking the Bicyclo[222]diazaoctane Rimentioning
confidence: 72%
See 2 more Smart Citations
“…Unlike notoamide B, metabolites tentatively identified by HPLC-MS as dihydrotalathermophilins A and B appear to be efficiently converted into the talathermophilins A and B, which, according to metabolite profiling, appear to be the end-products. Indeed these dihydrotalathermophilins A and B were recently structure elucidated 58b and named talathermophilin C and D. There were no indications of other metabolites with a bicyclo[2.2.2]diazaoctane ring system and/or any of the spiro -compunds of the notoamide type in Talaromyces thermophilus , where glycine or alanine analogues of the proline-derived metabolites discussed here could theoretically have been secondary metabolites in this themophilic species.…”
Section: Related Metabolites Lacking the Bicyclo[222]diazaoctane Rimentioning
confidence: 72%
“…57 P. westlingii was treated as a synonym of P. waksmanii by Pitt, 37 but has later been shown to be a valid species. 35a,57 Talaromyces thermophilus strain YM 1-3 produces talathermophilins A and B, 58 secondary metabolites related to notoamide E, except that glycine or alanine is replacing proline and the end-products have a double-bond conjugating one of the ketones in the dioxopiperazine to the indole part of the molecule. We have found that the glycine and alanine notoamide E analogues (without the extended conjugation) are also formed in Talaromyces thermophilus CBS 116.72, albeit accumulated in much smaller amounts compared to the end-products.…”
Section: Related Metabolites Lacking the Bicyclo[222]diazaoctane Rimentioning
confidence: 99%
See 1 more Smart Citation
“…Thermophilic fungi received little attention though strains keyed out as Aspergillus clavatus (Jiang et al ) and Talaromyces thermophilus (Chu et al ; Guo et al ) have been reported.…”
Section: High‐temperature Environmentsmentioning
confidence: 99%
“…com.). Aspergillus clavatus(Jiang et al 2013) and Talaromyces thermophilus(Chu et al 2010;Guo et al 2011) have been reported.…”
mentioning
confidence: 99%